PENGARUH CURRENT RATIO, RETURN ON EQUITY DAN DEBT TO ASSET RATIO TERHADAP PRICE BOOK VALUE PERUSAHAAN ADVERTISING, PRINTING DAN MEDIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2014-2017 - Bayu Nur Batin; Deny Ismanto (Universitas Ahmad Dahlan, 2019)
This research was conducted with the aim of partially testing the influence of Current Ratio, Return On Equity, and Debt to Asset Ratio on Price Book Value to Advertising, Printing and Media companies listed on the Indonesia Stock Exchange (IDX). Factors that influence price book value (PBV) include liquidity that is proxied by current ratio or current ratio (CR), profitability projected with return on equity (ROE), and Debt to asset ratio (DAR). The research period was carried out for 4 (four) years, namely 2014-2017. This type of research is Quantitative data, namely data in the form of numbers, or Quantitative data that are sent in a queue. The population in this study is a company engaged in the services of Advertising, Printing, and Media services listed on the IDX, namely 15 companies. The sample in this study was obtained by purposive sampling method. Based on existing criteria, 15 companies were obtained. Hypothesis testing is done by Multiple regression analysis, but before testing hypotheses first testing the classical assumptions. The results of hypothesis testing are carried out partially, namely the t test shows that CR has no effect and is not significant on PBV. ROE has a partial and significant effect on PBV. DAR partially has no effect and is not significant for PBV.